Gender ratio in undergraduate medical program, Medical Faculty, IIUM. - Myint, Yi Yi; Tun, Ye (Kulliyyah of Medicine, International Islamic University Malaysia, 2008)
Background: Historically, more men enrolled in medical schools than women. However, during the last few decades, there has been an increase in the number of women attending medical schools worldwide. Although a similar trend is seen, there is no documentation found in Malaysia. In this present study, we investigated if such gender enrolment differences occurred at our medical school. Methods: Information was obtained from Kulliyyah of Medicine student statistic for 2006/2007 section and graduates from 2001/2002 (1st batch) to 2006/2007. Results: Our study showed that more than half (60%)of our students are female and all students who received distinction in final year exam from 2002 till now are females although the number of males who needed to sit for the supplementary examination outnumbered the females during that period. Discussion: The feminization of medicine in International Islamic University Malaysia (IIUM) was similar to other studies worldwide. Further research should be aimed on comparison of the academic performance of male and female medical students and also choice of specialty chosen by men and women in our university.